Performance Analysis of NFS Protocol Usage on VMware ESXi Datastore - Billy Susanto Panca (Maranatha University Press, 2017)
Hypervisor virtualization that uses bare metal architecture allows to allocate and provide resources for each created virtual machines. Resources such as: CPU and memory, can be added or upgraded anytime to the host hardware (virtualization server) to be able to create more virtual machines. However, upgrading the hard drive size cannot be done anytime if there are already have data or virtual machine that has fully operated on the host hardware, related to the raid system and the establishment of hard drive partition.Upgrading hard drive size on virtualization server can be done by using NFS protocol on NAS server. VSphere ESXi able to use NFS protocol and store the virtual disk that is used by virtual machine as guest operating system on network storage besides using local hard drive (host hardware hard drive). When the virtual machine want to run the guest operating system, it will request to write/read virtual disk there is stored on NAS by using NFS protocol through the network.In this research, measurements has been taken on data communication performance due the usage of NFS as virtual machine’s datastore in addition to local hard drive usage on server’s device. Measurements were performed by sending various data size from client to server (virtual machine) and measure write/read speed on server’s cache memory and hard drive, and measure RTT (Round-trip Time) delay between client-server. The testing has been conducted on virtual machines that use local drive and NFS as virtual disk datastore.